PHYSICAL HEALTH CHARACTERISTICS OF YOUNG SCHOOL-AGE CHILDREN WHO ARE ENGAGED IN SPORTS DANCE (Physical Culture and Sport: Scientific Perspective, 2025)
The study, which is devoted to the physical health of primary school children, was attended by 48 students aged 8-9 years, of which 28 were girls and 20 were boys. The assessment of physical health was carried out according to the generally accepted method of G.L. Apanasenko. The article considers the importance of motor activity in the life of primary school children, the importance of sports dances for physical, psycho-emotional development and the impact on physical health. It is also noted that the organization of extracurricular activities and the personality of the coach play an important role in the effectiveness of attracting and improving the health of primary school children to sports dances. It is theoretically confirmed that an important factor is taking into account the individual characteristics of the respondents, their health status, age category, gender and motivation to attend classes. It is substantiated that in order to achieve greater involvement of primary school children in sports dances, it is necessary to use modern, innovative teaching methods, these can be dance trainings, interactive games that stimulate interest in classes. Analysis of anthropometric data showed that the average body weight of 8-year-old boys is =28.8 kg. (S=2.1), in 9-year-olds = 32.1 kg. (S=3.4), and the average values of 8-year-old girls are = 27.8 kg. (S=2.8), in 9-year-olds - = 29.5 kg. (S=1.6), the average body length data of 8-year-old boys is = 134.6 cm. (S=7.4), in 9-year-olds the indicators are equal to = 135.4 cm. (S=7.3), the results of 8-year-old girls are = 132.2 cm. (S=4.9), and 9-year-olds - = 133.1 cm. (S=6.4). The results of the chest circumference in 8-year-old boys are = 59.1 cm. (S=2.3), 9-year-olds showed the result = 62.3 cm. (S=1.6), the data of 8-year-old girls show the result = 57.9 cm. (S=1.2), 9-year-old girls received the indicators - = 61.8 cm. (S=1.2). It was established that the development of the cardiovascular system and anthropometric indicators correspond to sex-age norms. When analyzing physical health, it was found that only 8-year-old boys do not have a low level of health.
Keywords: sports dances; health; physical development; children; extracurricular activities